Effect of certain chemical surface treatments on repair bond strength of some denture base materials - Reem Ahmed Shihab; Basima M Hussein (College of Dentistry/ University of Baghdad, 2014)
Background: Fracture of different types of acrylic denture base is a common problem associated with dental prosthesis. Studies suggested that the repair strength may be improved by several means including surface treatment with chemical agents. The aim of the study was to evaluate the effect of surface treatment with acrybond-bonding agent and monomer on fractured denture base in respect to transverse, tensile and shear bond strength and evaluation of the mode of failure by light microscope. Materials and methods: Two hundred seventy specimens were prepared and divided into 3 groups according to the material used (regular conventional, rapid simplified and high impact) heat cure acrylic. The specimen in each groups were prepared specifically according to testing (tensile, transverse and shear bond strength). All the specimens were stored in 37C for 28days before fracture then the specimens in each test were divided into 3 groups according to surface treatment (control-without surface treatment, monomer(MMA) group and acrybond (MMA with acetone ))group. The specimens repaired with cold cure acrylic using Ivomet; then stored in distill water at 37C for 2days before testing. GEFRA universal testing machine was used and final load at fracture was recorded. Results: monomer and acrybond group exhibited higher bond strength than control group. Conclusion: the type of denture base affect the value of bond strength and the use of monomer or acrybond resulted in higher bond strength than untreated surface.